A EU EMMISSIONS TRADING SCHEME: RECENT DEVELOPMENTS - Chevleski, Aleksandar; Chudoska Blazevska, Irina; Gligorova, Anita (International Scientific Journal Vision, 2019)
In 2005 the EU has developed the world’s first multi-country cap-and-trade scheme for greenhouse gases. Today, 31 countries participate in the Scheme (the 28 EU Member States, Iceland, Liechtenstein and Norway), totalling population of half billion people. ETS includes more than 12 000 industrial plants and aircraft operators and entails half of European CO2 emissions. Under the Scheme, a quantitative limit on CO2 emissions was imposed and a market price has been paid for CO2 emissions by virtually all industrial and electricitygenerating installations within the European Union. Legally binding caps have strict timetable: the cap decreases by 1.74% per year from 2010 based on the average cap for 2008-12, the second phase of the EU ETS. This annual reduction factor of 1.74% has been fixed in order to reach an annual amount of carbon allowances 21% below 2005 levels by 2020. In 2014 the European Council decided the rate to be increased 2.2% a year from 2021, in order that a 43% reduction be attained by the ETS sectors by 2030 compared to 2005. These respective shares are determined by what is estimated to be a cost-effective contribution by the sectors covered to meet a 40% economy-wide target by 2030. The EU ETS became a effective key instrument of European climate change policy and the primary vehicle for meeting the obligations under the Kyoto Protocol and now the Paris Agreement. These particular article aims to give overview of the recent developments of this key EU instrument and offer insight in the future developments.